Kesetaraan Gender dan Pendidikan Humanis - Erda Fitriani; Neviyarni Neviyarni (Universitas Negeri Padang, 2022)
Gender equality is still a target for countries that are members of the SDGs, including Indonesia. Efforts to improve gender equality are mainly through education, both family education and school education. Gender responsive education has been carried out in Indonesia and has become a target for sustainable development with the SDGs program, which is targeted to be achieved by 2030. Various phenomena of gender inequality are still encountered in society. This shows that there are problems in the perception and application of gender equality. One of the efforts to give birth to justice and gender equality is through education. Therefore, this article aims to explain the concept of gender and gender equality and then gender equality education.